2020
DOI: 10.1088/1361-6528/ab8988
|View full text |Cite
|
Sign up to set email alerts
|

Desalination behavior analysis of interior-modified carbon nanotubes doped membrane by dielectric spectrum and molecular simulation

Abstract: Carbon nanotube (CNT)-doped polyamide (PA) membranes have attracted much attention in reverse osmosis (RO) membranes due to their significant advantages of water flux and desalination. In this study, we synthesized multi-walled carbon nanotube (MWNT)/PA RO membrane by 12-oxodidodecanoic acid methyl ester group interior-modified MWNTs (MWNT-C14H25O4). Then, their mechanism of desalination behavior was successfully analyzed by combining dielectric relaxation spectrum (DRS) and molecular dynamics (MD) simulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The strongly anisotropic thermal expansion is expected to affect the contact between the crystals and the matrix, and could lead to enhanced transport properties of the membrane. Additional experiments were carried out to study the dielectric properties of pristine and doped membranes using electrochemical techniques which are widely used to characterize the polarized membrane behavior [73][74][75] . It was observed that the doped membrane has 25% higher dielectric constant (ε = 2.74 ± 0.04) compared to the pristine membrane (ε = 2.06 ± 0.06) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The strongly anisotropic thermal expansion is expected to affect the contact between the crystals and the matrix, and could lead to enhanced transport properties of the membrane. Additional experiments were carried out to study the dielectric properties of pristine and doped membranes using electrochemical techniques which are widely used to characterize the polarized membrane behavior [73][74][75] . It was observed that the doped membrane has 25% higher dielectric constant (ε = 2.74 ± 0.04) compared to the pristine membrane (ε = 2.06 ± 0.06) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, perform molecular simulation of the PFEXs in Materials Studio to investigate the influence of different monomers on free volume from molecular dynamics. 26,27 A single polymer chain with 50 repeat units was constructed. After several geometric optimizations, its energy reached the minimum.…”
Section: Crystallinity Property Of Pfexsmentioning
confidence: 99%
“…The more stacked PA matrix in the direction of the flow led to lower flux in PA-CNT1, while the high flux in PA-CNT2 was a result of the guiding effect as well as less severe stacking caused by the CNT. Li et al 203 reported, through a joint experimental and MD study, high water flux across a membrane made of functionalized MWNT-C 14 H 25 O 4 and PA. The finding was attributed to the larger pore dielectric parameters, larger average pore diameter, and higher water volume fraction of the MWNT-C 14 H 25 O 4 /PA membrane.…”
Section: Studies On Tfnc Membranesmentioning
confidence: 99%